A comprehensive review of mucinous ovarian cancer: insights into epidemiology, risk factors, histological characteristics, and clinical outcomes - Gupta, Sumedha; Kalwaniya, Dheer Singh; Shamsunder , Saritha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mucinous ovarian cancer (MOC) represents a rare subtype within the spectrum of epithelial ovarian carcinoma (EOC). In contrast to a uniform approach applied to all EOC subtypes, MOC stands out as a distinctive entity. A nuanced understanding of the pathological features and genomic profile of MOC holds the potential for enhancing management strategies and, consequently, prognostic outcomes. The differentiation between primary MOC and metastatic mucinous carcinoma poses a challenge but is imperative for accurate clinical decision-making. Notably, early-stage MOC exhibits a favourable prognosis, while advanced disease is characterized by a less favourable outcome. Surgical intervention assumes a pivotal role both in the early stages and metastatic scenarios. Chemotherapy is typically initiated from stage II MOC onwards, with the conventional gynaecological protocol commonly employed; however, there is also precedent for the application of gastrointestinal (GI) regimens. Given the association of MOC with diverse molecular alterations, the consideration of targeted therapy emerges as a potential therapeutic avenue for this unique disease entity. The main tool used for this literature review was PubMed. MOC stands as a distinct entity within EOC subtypes, distinguished from GI mucinous carcinoma by its unique clinical behavior, pathological features, molecular profile, prognosis, and response to standard treatment. The challenges lie in both the diagnosis and treatment of MOC, emphasizing the complexity and specialized considerations required for managing this particular subtype of OC.